HER2-positive gastric cancer: from targeted therapy to CAR-T cell therapy - Shao, Qiangzu; Deng, Junge; Wu, Haoran; Huang, Zeping (Frontiers in Immunology, 2025)
Gastric cancer (GC) ranks as the fifth most prevalent cancer on a global scale, with HER2-positive GC representing a distinct subtype that exhibits more intricate biological characteristics. Conventional chemotherapy typically exhibits restricted efficacy in the management of HER2-positive GC. In light of the incessant advancement in molecular targeted therapies, targeting HER2 has emerged as a promising therapeutic approach for this subtype. The advent of antibody-drug conjugates (ADCs) and chimeric antigen receptor T-cell therapy (CAR-T) has furnished novel treatment alternatives for HER2-positive GC. Nevertheless, owing to the pronounced heterogeneity of GC and the complex tumor microenvironment, drug resistance frequently emerges, thereby substantially influencing the effectiveness of HER2-targeted therapy. This article comprehensively summarizes and deliberates upon the strategies of HER2-targeted therapy as well as the underlying resistance mechanisms.